Confidentiality of the notary deed in the freedom of the academic pulpit - Margiyanti, Reni; Negara, Tunggul Anshari Setia; Sjafi’i, R. Imam Rahmat (Jurnal Cakrawala Hukum, 2022)
Many academic community members abuse the academic pulpit's freedom for inappropriate purposes. The purpose of this paper is to analyze the conflict or conflict of norms in the Article related to the obligation of a Notary to keep everything regarding the Deed he made and the explanation of the Article associated with the freedom of the academic pulpit (Article 8 Paragraph (1), Law of the Republic of Indonesia Number 12 the Year 2012), in the Republic of Indonesia. On the one hand, a notary must keep everything about the deed he made secret; on the other hand, a notary who is a teaching staff or lecturer must carry out his duties as an academic civitas. This writing uses a normative juridical method with a statute and conceptual approach. The results obtained are that the position of a notary is higher than the position of a notary as a lecturer; therefore, the notary's limitations regarding the academic pulpit are to the position of a notary as a public official, whereas a public official a notary is obliged to keep everything related to the deed he made, which means that he has been ordered to a notary. Not to give, show or notify the act’s contents except those with a direct interest. Therefore, regulators should study further if there is a conflict of norms in the Articles related to the Notary's obligation to keep everything confidential regarding the Deed he made. How to cite item: Margiyanti, R., Negara, T., & Sjafi’i, R. (2022). Confidentiality of the notary deed in the freedom of the academic pulpit. Jurnal Cakrawala Hukum, 13(2), 182-193. DOI:https://doi.org/10.26905/idjch.v13i2.5735.